LA VALIDEZ DEL CONSENTIMIENTO EN ADOLESCENTES MAYORES DE CATORCE AÑOS DE EDAD EN DELITOS SEXUALES EN EL CÓDIGO ORGÁNICO INTEGRAL PENAL - Massa Pacheco, Michael David (2020)
The present legal investigation entitled: "The validity of consent in adolescents over fourteen years of age in sexual crimes in the Comprehensive Organic Criminal Code" presented under the thesis modality refers to a legal problem that deserves to be transformed to solve and overcome the problematic legal partner that is identified; establishing that the Constitution of the Republic of Ecuador enjoys supremacy in the hierarchical order of application of legal norms; Thus, article 175 establishes that children and adolescents will be subject to legislation and a specialized administration of justice, where the principles of the doctrine of integral protection will be applied, which is in harmony with Article 1 of the Children's Code. and Adolescence together with the principle of the best interest of childhood and adolescence. Regarding constitutional rights, people are recognized and guaranteed to make free, informed, voluntary and responsible decisions regarding their sexuality, according to number 9 of Art. 66 of the Supreme Law, this constitutional norm corresponds to the Ibero-American Convention on the Rights of Young People, establishing in article 23: "Sex education will be taught at all educational levels and will promote responsible conduct in the exercise of sexuality"; complementing this constitutional right with solid arguments established by the Constitutional Court where it mentions: it is only up to the adolescent to decide on their sexual and reproductive life and health, basing their decisions on the tools granted by the State, society and family, for the free, informed and responsible decision-making. For all the above, it is necessary to indicate that number 5 of article 175 of the Organic Comprehensive Criminal Code, 5 stipulates that in sexual crimes, the consent given by the victim under eighteen years of age is irrelevant, however, adolescents older than Fourteen years of age have the constitutional right to make free and voluntary decisions regarding their sexuality, for which reason said consent of the victim must be valid when judging sexual crimes, since the consent of the adolescent included in said age , excludes the criminal type by which it is intended to judge. By virtue of this, the validity of the consent of the victim over fourteen years of age, in sexual crimes, must be considered in the approach of this work. The theoretical, legal and doctrinal hoarding, as well as the application of surveys and interviews, allowed the successful legal investigation to be carried out, and an extensive investigation to be carried out on the subject, resulting in clear and precise foundations on the innovation of the regime. legal validity of consent in adolescents over fourteen years of age in sexual crimes. The analysis of the similarities and differences of one or more problems that Ecuadorian legislation presents with other countries, was carried out through Comparative Law, which provided a comprehensive study of the legal institution treated in this thesis work. The case study served as a fundamental support to clearly and precisely stipulate the solution to the problem dealt with in this legal investigation, taking as benchmarks, judgments of the highest constitutional control body such as the Constitutional Court of Ecuador and complementing with the Supreme Court of Justice of Peru with its plenary agreement regarding the validity of consent in adolescents in sexual crimes 6 Within the present legal investigation, the verification and contrast of objectives and hypotheses were also verified, using techniques of transfer, filing, surveys, interviews and field observation; jointly the foundations of the present legal investigation were cemented, by means of the methods used, among them: Scientific, Inductive, Deductive, Comparative, Exegetical, Doctrinary and Statistical. And as the main contribution of this investigation, the legal basis of the reform proposal that is sustained as a result of all the investigation, including the respective conclusions and recommendations. Therefore, the proposal for a real and possible solution is left within the analyzed topic.